Factors associated with the prevalence of anemia in pregnancy: A scoping review - Binti Lu'lu' Muthoharoh; Farida Kartini (Universitas Aisyiyah Yogyakarta, 2022)
Backgroud: Anemia initially begins with low hemoglobin with respect to the number and quality of healthy red blood cells decrease. It thereby reduces the oxygen transported in the tissues. Anemia is one of the main causes of maternal morbidity and mortality, especially in developing countries. During pregnancy, the expansion of red blood cell mass increases oxygen transport and iron transfer to the placenta and the fetus. Purpose: This study seeks to determine the factors associated with the prevalence of anemia in pregnant women. Method: The method used consisted of five stages of the identification of scooping review questions with the PEOS framework (Population, Exposure, Outcomes, Study). The identification of relevant articles was carried out usingdatabases such as Wiley Online Library, PubMed, andProQuest. Article selection employedThe Joana Briggs Institute, data charting as well as arranging, summarizing, and reporting the results. Results: From 105 articles, 44 articles with relevant titles and abstracts were obtained. 9 articles met the inclusion and exclusion criteria. Five factors associated with the prevalence of anemia in pregnancy were found. They are maternal age, gestational age, parity, birth spacing, and socioeconomic factor. Conclusion: This study concludes that five factors associated with the prevalence of anemia among pregnant women are maternal age, gestational age, parity, birth spacing, and socio-economic factor.